Category Shift in the Story of the First Day of World’s Creation on Genesis - Yesia Kristadella; Ni Ketut Alit Ida Setianingsih; I Gusti Agung Istri Aryani (Pusat riset dan Inovasi Nasional, 2025)
This paper is made in order to analyze the structure shifts in the story of the first day of world’s creation on Genesis. Category shifts refer as a grammatical or structural components change during translation between a source language (SL) and a target language (TL). This research aimed to find what type of category shift used and how the category shift implied in the story of the first day of world’s creation on Genesis. The study revealed that all types of category shifts were used in total of 25 occurrences. Structure shift was found occurring 20% (5 times), class shift was found occurring 36% (9 times), unit shift was also found occurring 36% (9 times) including 8% of low to high unit shift (2 occurrences) and 28% of high to low unit shift (7 occurrences), and intra-system shift was found occurring 8% (2 times). Class shifts and unit shifts were the most frequently occurring while intra-system shift were the least. Keywords: Translation, Category Shift, Biblical Text